A high-efficiency defluorination material and preparation method thereof
By using magnesium salts and rare earth salts to prepare fluorine adsorbent materials for crosslinked microsphere carriers, the problems of complex and high cost of existing fluorine removal materials are solved, and fluorine ions in fluorine-containing wastewater are efficiently removed and good recycling and regeneration performance is achieved.
Patent Information
- Application Number
- CN202411785729.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing fluorine-removing materials have complex preparation processes and high production costs, making it difficult to effectively remove fluorine ions in fluorine-containing wastewater, and there is a problem of secondary pollution.
Magnesium salt and rare earth salt are used as raw materials, and fluorine adsorption materials with high adsorption capacity and circulation regeneration properties are prepared by adding template agents, carriers and precipitants, and heating and hydrothermal reactions. The carrier is a crosslinked microsphere, which is obtained by crosslinking a chitosan modification with ethylene glycol diglycidyl ether.
It has achieved efficient removal of fluorine ions in fluorine-containing wastewater, strong adsorption capacity, good recycling and regeneration performance, reduced production costs and avoided secondary pollution.
Smart Images

Figure CN119236905B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a high-efficiency defluorination material and a preparation method thereof. Background Art
[0002] At present, the reported methods for removing fluorine from fluorine-containing wastewater include chemical precipitation, coagulation precipitation, adsorption, ion exchange, membrane filtration, electrochemical method and induced crystallization. At present, for large-scale fluorine-containing wastewater with high concentration, the domestic use of multi-stage precipitation process combining chemical precipitation and coagulation precipitation is more and more common. However, since calcium fluoride itself has a certain solubility and will dissolve with calcium hydroxide, this often leads to the fluorine content in the treated wastewater still being 20-30 mg / L, which is difficult to meet the discharge standard. At the same time, there are problems such as large amount of sludge, serious secondary pollution, and greatly increased effluent salinity. Compared with other methods, the adsorption method has the characteristics of simple operation and stable effluent water quality, and is increasingly valued. Therefore, the development of green and environmentally friendly defluorination materials to achieve the goals of low cost, high efficiency and no secondary pollution of high-fluorine-containing wastewater is a technical bottleneck that needs to be urgently solved in the treatment of high-fluorine-containing wastewater. Among the different types of adsorption materials that have been reported, rare earth-based materials have attracted more and more attention due to their strong adsorption activity and large adsorption capacity, and have good application prospects.
[0003] Existing patent documents such as CN117534169B and CN116237023B all use rare earth compounds as the main raw materials to adsorb and remove fluoride ions from water, but they all have the disadvantages of complex preparation processes and high energy consumption, which leads to high production costs and thus increases water treatment costs. In order to solve the above problems, this patent invents a fluorine adsorption material with a simple preparation process and good adsorption effect to meet the actual needs of industrial enterprises for fluoride-containing wastewater treatment. Summary of the invention
[0004] The purpose of the present invention is to provide a high-efficiency defluorination material and a preparation method thereof, so as to solve the problems of complex preparation process and high production cost of existing defluorination materials, and to improve the defluorination efficiency to meet the actual needs of fluorine-containing wastewater treatment.
[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0006] The present invention discloses a method for preparing a fluorine adsorption material, comprising:
[0007] First, magnesium salt and rare earth salt are added to water to obtain a mixed solution, a template solution and a carrier are added to the mixed solution and heated, and then a precipitant solution is added to react to obtain a precursor, and the precursor is subjected to a hydrothermal reaction to separate a precipitate, and the precipitate is washed and dried to obtain a fluorine adsorption material; the carrier is a cross-linked microsphere, and the cross-linked microsphere is obtained by cross-linking a chitosan modifier with ethylene glycol diglycidyl ether. The cross-linked microsphere is used as a raw material for preparing a fluorine adsorption material. The cross-linked microsphere itself can adsorb fluoride ions through electrostatic attraction, and can also be used as a good carrier to load rare earth ions with high adsorption to form a complex, thereby obtaining a fluorine adsorption material with high adsorption capacity and recycling performance.
[0008] Preferably, the magnesium salt is at least one of magnesium chloride, magnesium nitrate and magnesium sulfate, and the amount of the magnesium salt added to the water is 4-5.3 g / L.
[0009] Preferably, the rare earth salt is at least one of lanthanum chloride, lanthanum nitrate, lanthanum sulfate, cerium chloride, cerium nitrate and cerium sulfate, and the amount of the rare earth salt added to the water is 40-55 g / L.
[0010] Preferably, the template solution is obtained by adding the template to water, the amount of the template added to the water is 7-7.5 g / L, the volume ratio of the template solution to the mixed solution is 1:1.8-2.3, and the template is hexadecyltrimethylammonium bromide.
[0011] Preferably, the amount of the carrier added to the mixed solution is 1.5-4 g / L.
[0012] Preferably, the precipitant solution is obtained by adding the precipitant to water, the amount of the precipitant added to the water is 100-107 g / L, the volume ratio of the amount of the precipitant solution used to the amount of the mixed solution used is 1:0.8-1.2, and the precipitant is diethylenetriamine.
[0013] Preferably, the heating temperature is 35-45° C., the reaction time of adding the precipitant solution is 110-150 min, and the reaction pH is 8-10.
[0014] Preferably, the reaction temperature of the hydrothermal reaction is 130-170° C., and the reaction time is 10-15 h.
[0015] The present invention also discloses a fluorine adsorption material, including the fluorine adsorption material prepared by any of the above methods.
[0016] The present invention discloses a method for preparing cross-linked microspheres, which is specifically:
[0017] Chitosan is added to water and the pH is adjusted to 4-4.8 to obtain a dissolving solution. Under nitrogen conditions, 3,5-diaminosalicylic acid is added to the dissolving solution, followed by a mixture of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide, N-hydroxysuccinimide and water. The mixture is reacted at 23-27°C for 2.5-3.5 hours to obtain a product solution. The product solution is dialyzed in water and dried to obtain a chitosan modification. The chitosan modification is added to an acetic acid solution, and then added dropwise to a sodium hydroxide solution to react for 3-5 hours to obtain microspheres. The microspheres are mixed with ethylene glycol diglycidyl ether and reacted at 23-27°C for 0.8-1.5 hours to obtain cross-linked microspheres.
[0018] Preferably, the mass ratio of the amount of chitosan used to the amount of water used is 1:95-100.
[0019] Preferably, the reagent used to adjust the pH is a hydrochloric acid solution, which is composed of hydrochloric acid and water, and the dosage ratio of hydrochloric acid to water is 1g:5-6ml.
[0020] Preferably, the mass ratio of the amount of chitosan used to the amount of 3,5-diaminosalicylic acid used is 1:1-1.5.
[0021] Preferably, the mass ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide to 3,5-diaminosalicylic acid is 1:1-1.5.
[0022] Preferably, the mass ratio of N-hydroxysuccinimide to 3,5-diaminosalicylic acid is 1:0.6-1.
[0023] Preferably, the ratio of N-hydroxysuccinimide to water in the mixed solution is 1 g:43-48 ml.
[0024] Preferably, the ratio of the chitosan modification to the acetic acid solution is 1 g: 47-53 ml.
[0025] Preferably, the acetic acid solution consists of acetic acid and water, and the volume ratio of the amount of acetic acid used to the amount of water used is 1:48-52.
[0026] Preferably, the sodium hydroxide solution consists of sodium hydroxide and water, and the dosage ratio of sodium hydroxide to water is 1g:22-28ml.
[0027] Preferably, the microspheres are mixed with ethylene glycol diglycidyl ether in a mass ratio of 1:0.45-0.55.
[0028] More preferably, in the preparation of the fluorine adsorbent material, an amphiphilic surfactant solution can be added on the basis of using the hexadecyltrimethylammonium bromide solution and the cross-linked microspheres. The coordinated use of the amphiphilic surfactant solution can modify the surface of the cross-linked microspheres and enrich the surface groups of the cross-linked microspheres, thereby improving the loading capacity for rare earth ions and the adsorption capacity for fluorine ions, and further improving the adsorption capacity and recycling performance of the prepared fluorine adsorbent material.
[0029] Preferably, the amphiphilic surfactant solution is obtained by adding the amphiphilic surfactant to water, the amount of the amphiphilic surfactant added to the water is 2.1-2.8 g / L, and the volume ratio of the amount of the amphiphilic surfactant solution used to the amount of the mixed solution used is 1:1.8-2.4.
[0030] The present invention discloses a method for preparing an amphiphilic surfactant, which specifically comprises:
[0031] 4,4'-dibromodiphenyl sulfone is added to acetone and heated to 50-60°C, followed by dripping octyl dimethyl tertiary amine and N,N-dimethylbenzylamine to react for 5-8 hours, standing to separate to obtain a white precipitate, which is then washed, purified and dried to obtain an intermediate. The intermediate is added to dichloromethane, followed by dripping chlorosulfonic acid dichloromethane solution, heated to 28-33°C to react for 2-3 hours, and after the reaction is completed, a crude product is obtained after neutralization, drying, washing and filtering, and finally ethanol is added to the crude product for extraction and drying to obtain an amphiphilic surfactant.
[0032] Preferably, the amount of 4,4'-dibromodiphenyl sulfone added to acetone is 0.035-0.045 g / ml.
[0033] Preferably, the mass ratio of the amount of octyl dimethyl tertiary amine used to the amount of 4,4'-dibromodiphenyl sulfone used is 1:0.5-0.8.
[0034] Preferably, the mass ratio of the amount of N,N-dimethylbenzylamine used to the amount of 4,4'-dibromodiphenyl sulfone used is 1:1.1-1.7.
[0035] Preferably, the amount of dichloromethane added to the intermediate is 0.1-0.16 g / ml.
[0036] Preferably, the chlorosulfonic acid dichloromethane solution is obtained by dissolving chlorosulfonic acid in dichloromethane, and the amount of chlorosulfonic acid added to dichloromethane is 0.02-0.04 g / ml.
[0037] Preferably, the usage ratio of the intermediate to the dichloromethane solution of chlorosulfonic acid is 1 g: 20-23 ml.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention provides a high-efficiency fluorine removal material and a preparation method thereof. A magnesium salt and a rare earth salt are added to water to obtain a mixed solution, and then a template solution and a carrier are added to heat the mixed solution, and then a precipitant solution is added to react to obtain a precursor, and the precursor undergoes a hydrothermal reaction to separate a precipitate, and finally washed and dried to obtain a fluorine adsorption material; the carrier is a cross-linked microsphere, and the cross-linked microsphere is obtained by cross-linking a chitosan modifier with ethylene glycol diglycidyl ether; the high-efficiency fluorine removal material prepared by the present invention has a strong adsorption capacity, has a high adsorption capacity for fluoride ions, can be recycled for multiple times, and has good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0041] Figure 1 This is the infrared spectrum of chitosan modification. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0044] Embodiment 1:
[0045] Preparation of fluorine adsorption material: First, magnesium chloride and lanthanum chloride are added to water to obtain a mixed solution, and hexadecyl trimethyl ammonium bromide solution is added to the mixed solution and heated to 40°C. Then, diethylenetriamine solution is added and the pH is adjusted to 9, and the reaction is continued for 120 minutes to obtain a precursor. The precursor is transferred to a hydrothermal reactor and reacted at 150°C for another 12 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with water and ethanol, and finally dried to obtain a fluorine adsorption material. The amount of magnesium chloride added to the water is 4.76 g / L, the amount of lanthanum chloride added to the water is 49.05 g / L, the cetyltrimethylammonium bromide solution is obtained by adding cetyltrimethylammonium bromide to water, the amount of cetyltrimethylammonium bromide added to water is 7.29 g / L, and the volume ratio of the use amount of the cetyltrimethylammonium bromide solution to the use amount of the mixed solution is 1:2, and the diethylenetriamine solution is obtained by adding diethylenetriamine to water, the amount of diethylenetriamine added to water is 103.17 g / L, and the volume ratio of the use amount of the diethylenetriamine solution to the use amount of the mixed solution is 1:1.
[0046] Embodiment 2:
[0047] Preparation of fluorine adsorbent material: First, magnesium nitrate and cerium nitrate are added to water to obtain a mixed solution, and hexadecyl trimethyl ammonium bromide solution is added to the mixed solution and heated to 60°C. Then, diethylenetriamine solution is added and the pH is adjusted to 11, and the reaction is continued for 120 minutes to obtain a precursor. The precursor is transferred to a hydrothermal reactor and reacted at 120°C for another 18 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with water and ethanol, and finally dried to obtain a fluorine adsorbent material. The amount of magnesium nitrate added to the water is 4.44 g / L, the amount of cerium nitrate added to the water is 104.54 g / L, the cetyltrimethylammonium bromide solution is obtained by adding cetyltrimethylammonium bromide to water, the amount of cetyltrimethylammonium bromide added to water is 18.23 g / L, and the volume ratio of the use amount of cetyltrimethylammonium bromide solution to the use amount of the mixed solution is 1:3.5, and the diethylenetriamine solution is obtained by adding diethylenetriamine to water, the amount of diethylenetriamine added to water is 154.76 g / L, and the volume ratio of the use amount of diethylenetriamine solution to the use amount of the mixed solution is 1:0.88.
[0048] Embodiment 3:
[0049] Preparation of fluorine adsorption material: First, magnesium sulfate and lanthanum sulfate are added to water to obtain a mixed solution, and hexadecyl trimethyl ammonium bromide solution is added to the mixed solution and heated to 50°C. Then, diethylenetriamine solution is added and the pH is adjusted to 11, and the reaction is continued for 60 minutes to obtain a precursor. The precursor is transferred to a hydrothermal reactor and reacted at 180°C for another 24 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with water and ethanol, and finally dried to obtain a fluorine adsorption material. The amount of magnesium sulfate added to the water is 12.04 g / L, the amount of lanthanum sulfate added to the water is 70.02 g / L, the cetyltrimethylammonium bromide solution is obtained by adding cetyltrimethylammonium bromide to water, the amount of cetyltrimethylammonium bromide added to water is 10.94 g / L, and the volume ratio of the use amount of cetyltrimethylammonium bromide solution to the use amount of the mixed solution is 1:2.5, and the diethylenetriamine solution is obtained by adding diethylenetriamine to water, the amount of diethylenetriamine added to water is 61.9 g / L, and the volume ratio of the use amount of diethylenetriamine solution to the use amount of the mixed solution is 1:0.37.
[0050] Embodiment 4:
[0051] Preparation of cross-linked microspheres: chitosan was added to water and the pH was adjusted to 4.5 with hydrochloric acid solution to obtain a solution. Under nitrogen conditions, 3,5-diaminosalicylic acid was added to the solution, followed by a mixture of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide, N-hydroxysuccinimide and water. The solution was reacted at 25°C for 3 hours to obtain a product solution. The product solution was dialyzed in water and dried to obtain a chitosan modification. The chitosan modification was added to an acetic acid solution and then added dropwise to a sodium hydroxide solution to react for 4 hours to obtain microspheres. The microspheres were mixed with ethylene glycol diglycidyl ether and reacted at 25°C for 1 hour to obtain cross-linked microspheres. The mass ratio of chitosan to water is 1:99, the hydrochloric acid solution is composed of hydrochloric acid and water, the mass ratio of hydrochloric acid to water is 1g:5.48ml, the mass ratio of chitosan to 3,5-diaminosalicylic acid is 1:1.25, the mass ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide to 3,5-diaminosalicylic acid is 1:1.36, the mass ratio of N-hydroxysuccinimide to 3,5-diaminosalicylic acid is 1:0.82, and the mass ratio of N-hydroxysuccinimide to water in the mixed solution is 1g:45.45ml. The mass ratio of chitosan modification to acetic acid solution is 1g:50ml, the acetic acid solution is composed of acetic acid and water, the volume ratio of acetic acid to water is 1:50, and the sodium hydroxide solution is composed of sodium hydroxide and water, the mass ratio of sodium hydroxide to water is 1g:25ml. The microspheres were mixed with ethylene glycol diglycidyl ether at a mass ratio of 1:0.5.
[0052] Preparation of fluorine adsorption material: First, magnesium chloride and lanthanum chloride are added to water to obtain a mixed solution, and hexadecyl trimethyl ammonium bromide solution and cross-linked microspheres are added to the mixed solution, and heated to 40°C. Then, diethylenetriamine solution is added and the pH is adjusted to 9, and the reaction is continued for 120 minutes to obtain a precursor. The precursor is transferred to a hydrothermal reactor and reacted at 150°C for another 12 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with water and ethanol, and finally dried to obtain a fluorine adsorption material. The amount of magnesium chloride added to the water is 4.76 g / L, the amount of lanthanum chloride added to the water is 49.05 g / L, the cetyltrimethylammonium bromide solution is obtained by adding cetyltrimethylammonium bromide to water, the amount of cetyltrimethylammonium bromide added to water is 7.29 g / L, and the volume ratio of the use amount of cetyltrimethylammonium bromide solution to the use amount of the mixed solution is 1:2, the amount of cross-linked microspheres added to the mixed solution is 2 g / L, and the diethylenetriamine solution is obtained by adding diethylenetriamine to water, the amount of diethylenetriamine added to water is 103.17 g / L, and the volume ratio of the use amount of diethylenetriamine solution to the use amount of the mixed solution is 1:1.
[0053] Embodiment 5:
[0054] The preparation of cross-linked microspheres is the same as in Example 4.
[0055] Preparation of fluorine adsorption material: The preparation of fluorine adsorption material in this embodiment is compared with that in Example 4, except that the amount of cross-linked microspheres added to the mixed solution is 3 g / L, and other conditions and parameters are the same as in Example 4.
[0056] Embodiment 6:
[0057] The preparation of cross-linked microspheres is the same as in Example 4.
[0058] Synthesis of amphiphilic surfactant: 4,4'-dibromodiphenyl sulfone was added to acetone to obtain a mixed solution, which was heated to 55°C, and then octyl dimethyl tertiary amine and N,N-dimethylbenzylamine were dripped into the mixed solution, and the reaction was continued for 6 hours. After the reaction was completed, the mixture was allowed to stand to obtain a white precipitate, which was washed, purified and dried to obtain an intermediate. The intermediate was added to dichloromethane to obtain a dissolving solution, and then a chlorosulfonic acid dichloromethane solution was dripped into the dissolving solution, heated to 30°C and reacted for 2.5 hours. After the reaction was completed, the crude product was obtained by neutralization, drying, washing and filtration. Ethanol was added to the crude product for extraction and drying to obtain an amphiphilic surfactant. The amount of 4,4'-dibromodiphenyl sulfone added to acetone is 0.04 g / ml, the mass ratio of octyl dimethyl tertiary amine to 4,4'-dibromodiphenyl sulfone is 1:0.63, the mass ratio of N,N-dimethylbenzylamine to 4,4'-dibromodiphenyl sulfone is 1:1.49, the amount of dichloromethane added to the intermediate is 0.137 g / ml, the chlorosulfonic acid dichloromethane solution is obtained by dissolving chlorosulfonic acid in dichloromethane, the amount of chlorosulfonic acid added to dichloromethane is 0.03 g / ml, and the amount ratio of the intermediate to the chlorosulfonic acid dichloromethane solution is 1 g:21.33 ml.
[0059] Preparation of fluorine adsorption material: First, magnesium chloride and lanthanum chloride are added to water to obtain a mixed solution, and hexadecyl trimethyl ammonium bromide solution, amphiphilic surfactant solution and cross-linked microspheres are added to the mixed solution, and heated to 40°C. Then, diethylenetriamine solution is added and the pH is adjusted to 9, and the reaction is continued for 120 minutes to obtain a precursor. The precursor is transferred to a hydrothermal reactor and reacted at 150°C for another 12 hours. After the reaction is completed, the precipitate is separated by centrifugation, washed with water and ethanol, and finally dried to obtain a fluorine adsorption material. The amount of magnesium chloride added to the water is 4.76 g / L, the amount of lanthanum chloride added to the water is 49.05 g / L, the hexadecyltrimethylammonium bromide solution is obtained by adding hexadecyltrimethylammonium bromide to water, the amount of hexadecyltrimethylammonium bromide added to water is 7.29 g / L, and the volume ratio of the use amount of the hexadecyltrimethylammonium bromide solution to the use amount of the mixed solution is 1:2, the amphiphilic surfactant solution is obtained by adding the amphiphilic surfactant to water, the amount of the amphiphilic surfactant added to water is 2.5 g / L, and the volume ratio of the use amount of the amphiphilic surfactant solution to the use amount of the mixed solution is 1:2, the amount of cross-linked microspheres added to the mixed solution is 2 g / L, and the diethylenetriamine solution is obtained by adding diethylenetriamine to water, the amount of diethylenetriamine added to water is 103.17 g / L, and the volume ratio of the use amount of the diethylenetriamine solution to the use amount of the mixed solution is 1:1.
[0060] Embodiment 7:
[0061] The preparation of cross-linked microspheres is the same as in Example 4.
[0062] The synthesis of the amphiphilic surfactant was the same as in Example 6.
[0063] Preparation of fluorine adsorbent material: The preparation of fluorine adsorbent material in this embodiment is compared with that in Example 6, except that the amphiphilic surfactant solution is obtained by adding an amphiphilic surfactant to water, the amount of the amphiphilic surfactant added to the water is 2 g / L, the volume ratio of the amount of the amphiphilic surfactant solution used to the amount of the mixed solution used is 1:2, and other conditions and parameters are the same as in Example 4.
[0064] Comparative Example 1:
[0065] The preparation of cross-linked microspheres is the same as in Example 4.
[0066] Preparation of fluorine adsorption material: The preparation of fluorine adsorption material in this embodiment is compared with that in Example 4, except that the amount of cross-linked microspheres added to the mixed solution is 0.9 g / L, and other conditions and parameters are the same as in Example 4.
[0067] Comparative Example 2:
[0068] The synthesis of the amphiphilic surfactant was the same as in Example 6.
[0069] Preparation of fluorine adsorbent material: The preparation of fluorine adsorbent material in this embodiment is compared with that in Example 6, except that cross-linked microspheres are not used. Other conditions and parameters are the same as in Example 6.
[0070] Experimental Example 1:
[0071] The chitosan modification was characterized by infrared spectroscopy analysis of the chitosan modification in Example 4, with a scanning range of 500-4000 cm -1 The results are as follows Figure 1 As shown, 3435cm -1 Characteristic absorption peak of OH or NH, 2800-3000cm -1 -CH 3 and -CH 2 The characteristic absorption peak is 1604cm -1 is the characteristic absorption peak of CN, 1550cm -1 Nearby is the characteristic absorption peak of benzene ring C=C, 750-800cm -1 It is the characteristic absorption peak of benzene ring CH, 1081cm -1 It is the characteristic absorption peak of CO.
[0072] Experimental Example 2:
[0073] To test the application of fluorine adsorption materials in actual fluorine-containing wastewater, fluorine-containing wastewater from the integrated circuit industry was used as the treatment object, and the fluorine adsorption materials prepared in Examples 1-7 and Comparative Examples 1-2 were added respectively, and the reaction was carried out at 25°C for 120 minutes. After the reaction, the residual fluorine ion concentration in the fluorine-containing wastewater was measured. The fluorine ion concentration of the fluorine-containing wastewater was 590 mg / L, the pH was 3.9, and the amount of fluorine adsorption material added to the fluorine-containing wastewater was 3.5 g / L.
[0074] Table 1 Results of residual fluoride ion concentration in fluoride-containing wastewater
[0075]
[0076] The results are shown in Table 1. Compared with Example 4, the residual fluoride ion concentration of the fluorine adsorbent prepared in Example 4 after treating the fluorine-containing wastewater is lower than that in Example 1, indicating that the use of cross-linked microspheres in the preparation process of the fluorine adsorbent material can improve the adsorption capacity of fluoride ions; compared with Example 5, Example 4 shows that within a certain range, the increase in the amount of cross-linked microspheres used will improve the adsorption capacity of the prepared fluorine adsorbent material; compared with Example 6, Example 4 shows that in the preparation process of the fluorine adsorbent material, on the basis of using cross-linked microspheres, the addition of amphiphilic surfactants can further improve the adsorption capacity of the fluorine adsorbent material, and obtain wastewater with a lower residual fluoride ion concentration; compared with Example 7, Example 6 shows that within a certain range, the reduction in the amount of amphiphilic surfactants used will reduce the adsorption performance of the fluorine adsorbent material; compared with Comparative Example 1, Example 4 shows that the amount of cross-linked microspheres used needs to be at an appropriate value, and too low an amount will inhibit the adsorption capacity of the prepared fluorine adsorbent material; compared with Comparative Example 2, Example 6 shows that the amphiphilic surfactant needs to be used together with the cross-linked microspheres, and the use of amphiphilic surfactants alone has no obvious effect on the adsorption capacity of the prepared fluorine adsorbent material.
[0077] Experimental Example 3:
[0078] Determination of the cyclic regeneration performance, the cyclic regeneration adsorption efficiency of the fluorine adsorbent materials prepared in Examples 1-7 and Comparative Examples 1-2 was measured to evaluate the cyclic regeneration capacity of the fluorine adsorbent materials. First, the fluorine adsorbent materials prepared in Examples 1-7 and Comparative Examples 1-2 were added to the fluorine-containing wastewater, reacted at 25°C for 120 minutes for adsorption, separated after the adsorption was completed and added to the sodium hydroxide solution for analysis, soaked for 10 hours, washed with water, and finally dried and continued to be put into the fluorine-containing wastewater for another adsorption experiment, and then the above test was repeated for a total of 10 cycles. Adsorption efficiency = (fluorine ion concentration in the original fluorine-containing wastewater - residual fluorine ion concentration after adsorption) / fluorine ion concentration in the original fluorine-containing wastewater × 100%.
[0079] Table 2 Adsorption efficiency results after 10 cycles
[0080]
[0081] The results are shown in Table 2. Compared with Example 4, the fluorine adsorbent material prepared in Example 4 has an adsorption efficiency higher than that in Example 1 after 10 adsorption cycles, indicating that the use of cross-linked microspheres in the preparation process of the fluorine adsorbent material can improve the recycling performance of the fluorine adsorbent material; compared with Example 5, Example 4 shows that within a certain range, the increase in the amount of cross-linked microspheres used will improve the recycling performance of the prepared fluorine adsorbent material; compared with Example 6, Example 4 shows that in the preparation process of the fluorine adsorbent material, on the basis of using cross-linked microspheres, the addition of amphiphilic surfactants can further improve the recycling performance of the fluorine adsorbent material, and after 10 adsorption cycles, it still has a high adsorption efficiency; compared with Example 7, Example 6 shows that within a certain range, the reduction in the amount of amphiphilic surfactants used will reduce the recycling performance of the fluorine adsorbent material; compared with Comparative Example 1, Example 4 shows that the amount of cross-linked microspheres used needs to be at an appropriate value, and too low a value will inhibit the recycling performance of the prepared fluorine adsorbent material; compared with Comparative Example 2, Example 6 shows that the amphiphilic surfactant needs to be used together with the cross-linked microspheres, and the use of amphiphilic surfactants alone has no obvious effect on the recycling performance of the prepared fluorine adsorbent material.
[0082] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0083] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for preparing a fluorine adsorbent material, comprising: First, magnesium salt and rare earth salt are added into water to obtain a mixed solution, a template solution and a carrier are added into the mixed solution and heated, and then a precipitant solution is added to react to obtain a precursor, the precursor is subjected to a hydrothermal reaction to separate a precipitate, and the precipitate is washed and dried to obtain a fluorine adsorption material; the carrier is a cross-linked microsphere, and the cross-linked microsphere is obtained by cross-linking a chitosan modifier with ethylene glycol diglycidyl ether; The preparation of the cross-linked microspheres is specifically as follows: Chitosan is added to water and the pH is adjusted to 4-4.8 to obtain a dissolving solution. Under nitrogen conditions, 3,5-diaminosalicylic acid is added to the dissolving solution, followed by a mixture of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide and water, and the mixture is reacted at 23-27° C. for 2.5-3.5 hours to obtain a product solution. The product solution is dialyzed in water and dried to obtain a chitosan modification. The chitosan modification is added to an acetic acid solution, and then added dropwise to a sodium hydroxide solution to react for 3-5 hours to obtain microspheres. The microspheres are mixed with ethylene glycol diglycidyl ether, and the mixture is reacted at 23-27° C. for 0.8-1.5 hours to obtain cross-linked microspheres. The mass ratio of chitosan to 3,5-diaminosalicylic acid is 1:1-1.5; the microspheres are mixed with ethylene glycol diglycidyl ether in a mass ratio of 1:0.45-0.
55.
2. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The magnesium salt is at least one of magnesium chloride, magnesium nitrate and magnesium sulfate, and the amount of the magnesium salt added to the water is 4-5.3 g / L.
3. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The rare earth salt is at least one of lanthanum chloride, lanthanum nitrate, lanthanum sulfate, cerium chloride, cerium nitrate and cerium sulfate, and the amount of the rare earth salt added to the water is 40-55 g / L.
4. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The template solution is obtained by adding the template into water, the amount of the template added into the water is 7-7.5 g / L, the volume ratio of the amount of the template solution used to the amount of the mixed solution used is 1:1.8-2.3, and the template is hexadecyltrimethylammonium bromide.
5. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The amount of the carrier added to the mixed solution is 1.5-4 g / L.
6. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The precipitant solution is obtained by adding the precipitant into water, the amount of the precipitant added into the water is 100-107 g / L, the volume ratio of the amount of the precipitant solution used to the amount of the mixed solution used is 1:0.8-1.2, and the precipitant is diethylenetriamine.
7. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: Said The heating temperature is 35-45°C, the reaction time of adding the precipitant solution is 110-150 minutes, and the reaction pH is 8-10.
8. The method for preparing a fluorine adsorbent material according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 130-170° C., and the reaction time is 10-15 h.
9. A fluorine adsorbing material, comprising the fluorine adsorbing material prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A chitosan-based fluoride remover and its preparation method
CN116237023B
A deep defluorination material and its preparation method and application
CN117534169B
Efficient rare earth modified defluorination material and preparation method thereof
CN114870808A